RENT SEEKING: A STUDY OF RENT SEEKING PRACTICES AND RELATIONS BETWEEN RULERS AND BUSINESSMEN IN THE DECENTRALIZATION REGIME - Ammelia, Euis; Dian Mustika Intan; Intan Idiani (Politik Indonesia: Indonesian Political Science Review, 2024)
This simple article will describe the practice of rent seeking and the relationship between the rulers and entrepreneurs in the decentralized regime. The case study taken in this study is the corruption case of the Granting of Nickel Mining Business Permits by the Governor of Southeast Sulawesi Province (Nur Alam) in Buton Regency and Bombana Regency 2009-2014. This study was written to see the typology of rent seeking practices that occurred in the corruption case of nickel mining business permits in Buton Regency and Bombana Regency, Southeast Sulawesi Province in 2009-2014. Moreover, this study also looks further into the relationship between entrepreneurs and the rulers that occurred in the area. To answer and examine this problem, the author uses various KPK report documents and media reviews of various investigative reports related to the case, then abstracts it in the theoretical framework of rent seeking. The author realizes that this data collection model is too early to draw conclusions without conducting field studies. The temporary findings of this paper are that the practice of rent seeking in the decentralized regime illustrates that the practice of rent seeking has shifted to the regions in various forms such as bribery. Moreover, the author sees a tendency for other practices in the form of rent seizing, namely the practice of rent seeking that occurs when bureaucrats try to obtain the right to allocate rent generated from state institutions for their own personal interests as was done by Nur Alam, the Governor of Southeast Sulawesi Province. Moreover, the relationship between entrepreneurs and rulers in the author's view tends not to occur state capture, but what occurs is crony capitalism.